(untitled) (Biomedical Research and Therapy, 2017)
Cancer is one of the most leading causes of death all over the world. Great deal of effort has been made to find out new agents for cancer treatment. Cancer cell models for drug testing play a critical role in this process. In recent years, 3D cell models were proved to be more effective mimic structure and character of cancer cells in tumors than 2D cell culture, hence they present the effect of drug more accurate to in vivo result. Vietnam which is a tropical country has tremendous potential in cancer drug screening due to its diversity of herbals. However, 3D cancer cell model for testing toxicity of extracts and compounds still be a new concept. The study aimed to generate multicellular tumor spheroid (MCTS) of MCF7 cells using hanging drop technique, which is evaluated as a simple method to create separated spheroids, easy to controlled the size of spheroids and enable to apply to high-throughput screening system. By tracking the spheroid size, growth curve and the exhibition of necrotic core using PI staining, the results indicated that the number of 2500 cells/well gives the most suitable spheroids for anticancer drug screening with the diameter about 500µm and exhibit necrotic core in the 3rd day of seeding. Toxicity of Doxorubicine and Tirapazamine were tested on the model compared which MCF7 cells cultured in 2D condition. The results showed that IC50 of Dox on 3D MCF7 cells was nearly 50 times higher than monolayer MCF7 cells. By contrast, TPZ, the agent demonstrated to have strong toxicity in hypoxia condition, showed the stronger anticancer ability on 3D models than 2D (IC50 of TPZ on 3D models showed significantly lower versus 2D). These results confirmed the promising of MCF7 cells MCTS generated by hanging drop for drug testing.